2022
DOI: 10.51771/mj.v2i1.254
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Faktor Individu Dan Postur Kerja Dengan Keluhan Low Back Pain Penjahit Kecamatan Medan Baru

Abstract: Usaha sektor informal merupakan salah satu usaha yang memiliki risiko kesehatan yang cukup tinggi. Salah satu usaha informal yang banyak terdapat di Indonesia dan memiliki risiko kesehatan yang cukup tinggi adalah usaha menjahit. Tujuan penelitian ini untuk menganalisis hubungan faktor individu dan postur kerja dengan keluhan low back pain penjahit Kecamatan Medan Baru. Jenis penelitian ini adalah observasional analitik dengan pendekatan cross sectionalstudy. Populasi dalam penelitian ini adalah semua penjahit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Research by Syaputra et al (2022), who analyzed individual factors with the incidence of low back pain, found that work duration was the factor with the highest level of significance, namely with a p-value = 0.00. 15 Excessive work duration is one of the factors triggers for low back pain. The recommended duration to achieve work efficiency is around 6-8 hours a day.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research by Syaputra et al (2022), who analyzed individual factors with the incidence of low back pain, found that work duration was the factor with the highest level of significance, namely with a p-value = 0.00. 15 Excessive work duration is one of the factors triggers for low back pain. The recommended duration to achieve work efficiency is around 6-8 hours a day.…”
Section: Discussionmentioning
confidence: 99%
“…13 Results of research conducted by Cahyani et al (2020) also stated that there is no significant relationship between the risk of work posture and LBP in library employees. 14 Research related to the relationship between work posture and the incidence of LBP in tailors was conducted by Syaputra et al (2022), with the results showing that there is a relationship between work posture and LBP complaints. 15 The instruments used in this research were the Rapid Entire Body Assessment (REBA) to assess the risk of work posture and the Nordic Body Map (NBM) questionnaire to measure LBP complaints.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of people with LBP in Indonesia is unknown, but it is estimated that between 7.6% to 37% (Kementerian Kesehatan, 2018). In Medan City, a previous study reported the prevalence of LBP in tailors at 62,9% (Syaputra et al, 2022).…”
Section: Introductionmentioning
confidence: 94%
“…Pekerja mengeluh bahkan sangat sakit pada bagian tubuh tertentu, hal ini disebabkan sikap kerja tidak alamiah [29]. Hal tersebut dapat terjadi karena posisi tubuh pada saat bekerja mayoritas bertumpu pada satu kaki yang terlalu lama, membungkuk dan posisi leher sering menghadap ke bawah dengan waktu yang lama [30].…”
Section: Keluhan Msds Pada Penjahitunclassified